1984
DOI: 10.1111/j.1432-1033.1984.tb08499.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cyanogen-bromide-digested fibrinogen on the kinetics of plasminogen activation by urokinase

Abstract: The catalytic efficiency (kcat/Km) of hgh-molecular-mass urokinase for the activation of Glu-plasminogen is increased about 10-fold in the presence of CNBr-digested fibrinogen. This stimulation is similar to that observed with 6-aminohexanoic acid, and yields kinetic parameters comparable to those for the activation of Lysplasminogen by urokinase. The increase of the activation rate of Glu-plasminogen by urokinase in the presence of CNBr-Fg can thus be explained by a conformational change in the plasminogen mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0
1

Year Published

1985
1985
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 27 publications
2
16
0
1
Order By: Relevance
“…Clearly, there was little effect of 6-AHA binding to tPA as full-length tPA and protease were identical (overall, a slight inhibition of 14% was observed in both cases). A different mechanism operates in the case of uPA where the conformational change in Glu-plasminogen at around 2 mM 6-AHA, previously found (29), did produce an enhanced activation rate (3.2-fold stimulation in this case), in agreement with earlier findings (30). Activation by tPA was much less sensitive to this conformational change.…”
Section: And Equation 17)supporting
confidence: 80%
See 1 more Smart Citation
“…Clearly, there was little effect of 6-AHA binding to tPA as full-length tPA and protease were identical (overall, a slight inhibition of 14% was observed in both cases). A different mechanism operates in the case of uPA where the conformational change in Glu-plasminogen at around 2 mM 6-AHA, previously found (29), did produce an enhanced activation rate (3.2-fold stimulation in this case), in agreement with earlier findings (30). Activation by tPA was much less sensitive to this conformational change.…”
Section: And Equation 17)supporting
confidence: 80%
“…Previous studies have also suggested that the protease domain acts independently of the N-terminal, A-chain domains (34,44). It is interesting that the uPA system is stimulated in this way and is more sensitive to the conformation of plasminogen as affected by 6-AHA, fibrinogen fragments, or monoclonal antibodies to the 6-AHA binding site (30,45). Model 3 also assumes that only free plasminogen is available for reaction with cell-bound tPA if the correct "template" profile is to be obtained.…”
mentioning
confidence: 99%
“…Activation occurs with a comparable affinity for Glu-plasminogen, Lys-plasminogen and low-M, plasminogen, while the catalytic rate constant is comparable for Glu-plasminogen and low-M, plasminogen but somewhat higher for Lysplasminogen. We have previously studied the activation of Giu-plasminogen and Lys-plasminogen by two-chain highmolecular-weight urokinase [22], and observed that K, for Lys-plasminogen is about tenfold lower as compared to Gluplasminogen (5.4 pM and 53 pM respectively) while the k,,, is not significantly different (1.5 s-' and 1.7 respectively). In the presence of 1 mM Ahx, a concentration that saturates the high-affinity lysine-binding site of plasminogen [23], the affinity of pro-UK for Glu-plasminogen is not significantly influenced while the k,,, increases threefold.…”
Section: Discussionmentioning
confidence: 99%
“…Both pro-UK and plasminogen were carefully rechromatographed in order to eliminate traces of active enzymes, ensuring that the observed kinetics are not influenced by contaminating urokinase or plasmin. In all experiments involving Glu-plasminogen, initial activation rates are obtaincd under conditions where the amount of plasmin generated is small compared to the concentration of plasminogen ( < 0.1 5 % ) and conversion of Glu-plasminogen to Lys-plasminogen is not observed, as shown by a linear generation of plasmin in time [22].…”
Section: Discussionmentioning
confidence: 99%
“…29 Furthermore, the presence of CNBrfibrinogen accelerates tPA-mediated plasminogen activation more significantly than urokinase plasminogen activatormediated plasminogen activation. 30 The amidolytic assay, although lacking the ability to resolve activity in fine tissue locales, can provide information on net tPA activity within specific dissectible neural compartments in mice, and shows that tPA activity is significantly higher in the cortex when compared with the underlying sub-cortical structures and the cerebellum (Supplementary Figure S2).…”
Section: Discussionmentioning
confidence: 99%